1994
DOI: 10.1016/s0022-5347(17)35226-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sperm Bound Antibodies in Infertile Men with Varicocele: The Effect of Varicocele Ligation on Antibody Levels and Semen Response

Abstract: An increased level of antisperm antibodies has been demonstrated in infertile men with varicocele compared with normal fertile men, suggesting a possible cause and effect relationship. To evaluate the possible etiological role of antisperm antibodies in varicocele patients, we performed a prospective study of 32 infertile men undergoing varicocele ligation. Semen analyses and antisperm antibodies as measured by the immunobead test were performed preoperatively and postoperatively at 3 and 6 months. Of the infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 12 publications
1
25
2
6
Order By: Relevance
“…Therefore, Djaladat et al (2006) concluded that varicocelectomy could reduce ASA concentration. Knudson et al (1994) were not able to show any significant difference between pre-and post-varicocelectomy ASA concentrations. Bonyadi et al (2013) showed that varicocelectomy had no effect on semen ASA.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Therefore, Djaladat et al (2006) concluded that varicocelectomy could reduce ASA concentration. Knudson et al (1994) were not able to show any significant difference between pre-and post-varicocelectomy ASA concentrations. Bonyadi et al (2013) showed that varicocelectomy had no effect on semen ASA.…”
Section: Discussioncontrasting
confidence: 62%
“…Knudson et al (1994) reported ASA levels in 32 infertile patients with varicocele. In this study, 28% had positive immunobead test results, among which IgG was found to be bound to the surface of the spermatozoa in 100% and IgA in 86% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that the reduced ADC values observed in patients with varicocele may be related to these histopathological alterations. Unilateral varicocele has been known to cause an increase in both testicular temperature secondary to autoimmune and hormonal effects, according to the literature [19][20][21]. The reduced contralateral ADC values observed in our study may possibly be appearing as a result of these effects.…”
Section: Discussionsupporting
confidence: 58%